A statistical quality control study on Precision Springs Manila Inc. - Pasumbal, Ann Sheryl (College of Engineering, 2005)
A statistical quality control study is performed on Precision Springs Manila (PSK) Inc. from November to December 2004. Before the study is conducted, there was a large rejection rate of the actuator base product. The main problem that is investigated is wrong dimensions of the product in focus. Control charts are constructed for each critical point of the product. It is found out that the process is out of control for all these critical points, as shown by the nonrandom patterns of the plotted points. Based on the problem analysis done, the main cause is the operators? lack of training, lack of in-process inspection and machine failure. The study proponents then considered the financial viability of providing additional training, improving procedures and inspection. The estimated total cost that would be incurred would amount to Php 25,000, a small price considering the long term benefits of each recommendation.